A systematic review on materials, design, and manufacturing of swabs - Vedant Vashist; Neil Banthia; Swapnil Kumar; Prajwal Agrawal (Annals of 3D Printed Medicine, 2023)
From simple cleaning to metagenomic studies and now the detection of the SARS-2 virus, swabs are absorbent pads with handles that hold significant promise in several applications and properties. Furthermore, the swab is now used for a wide range of medical purposes, such as the collection of bacteria and other pathogens such as influenza and H1N1. Various designs and materials used for the tip have led to a wide range of applications. In this review, we discuss the characteristics of essential tip materials such as rayon, polyester, nylon, and polyurethane in the context of specimen collection from various substrates. Further, this article reviews swab manufacturing techniques, including injection molding and calendar roll pressing, among others. In recent years, advances in additive manufacturing technology have made it possible to produce swabs in a fast and efficient manner. Furthermore, the design for additive manufacturing (DfAM) is given for the production of swabs. We also examine how 3-D printing of bio-resin swabs has revolutionized the manufacturing process, making it autonomous, quicker, more efficient, and environmentally friendly. Additionally, a shortage of medical devices for testing the SARS-2 virus has zealously motivated the medical industry to revolutionize through additive manufacturing of swabs, thus revolutionizing the medical industry. In conclusion, the limitations of the current techniques and future directions for swabs are discussed.